(untitled) (MAUSAM, 2022)
INSAT-3D/3R Geosatellites are in orbit at 74 and 82 °E positins oerating in staggring mode of 15 minute temporal frequency providing contineous coverage in high spatial domain throgh 6 channel Imager. Satellite derived geophysical parameters like Outgoing Long wave Radiation (OLR), Land Surface Temperature (LST) and Upper Trpospheric Humidity etc are found to very useful in monitoring the high temperature weather episodes affecting almost entie country like Punjab, Hariyam Rajastham Uttar Pradesh (UP), Bihar, Madhra Pradesh (MP)P, , Maharastra, Andhra Paradesh (AP) , Telengana, Tamilnadu Orissa etc starting from mid of March-2022. The actual temperatures in the above said areas pesrsisting above normal ( 4 to 7 C) from Mid March to Mid April-2022 and caued heat wave conditiions in most of the places of the country. The persisteny of the prevaling heat wave conditions is not only related to surface features but also upper air anticyclonic circulations and sinking of dry air over the affected areas. The entire feedback cycle from lower to middle ttroposphere operating with dry air mass (Northerly) almost entire Northwest , Central and parts of South (Maharastra, AP and Telengana) and keep the areas warm and above normal temperature range. The eastward moving systems also not reaching to lower northern latutudes and moving away and keeping away misture laden winds. This paper brought out the role of INSAT-3D/3R satellite derived products in monitoring such high temperature episodes. Such type of weather events blended with the support of climatologial features of prevailing weather systems of the season can be utilized in forecasting and its persistence over the area. It is seen from the study that, the OLR vales threshold ranges from 330 -380 watt /m2 in pockets of warmer temperatures or suffering from heat wave conditions. Similarly, the Land surface temperature and UTH values 306 -325 °K & 05-25 % respectively. The IPWV values in mm are also varies from 2-12 mm during mid-March to mid-April-2022. The satellite and climatological information can be clubbed together up to village level to help the society and disaster management authorities at state /district level in advance of such high impact weather events. This study is done with limited data sets and in future, it will be carrid out for larger doimain and a suitable the long period avarage (LPA) of past INSAT data (daily, monthly, seasonal), so that areawise thresholds can be generated from almost for entire Indian domain.